A remarkable new genus and two new species of the Gigantometopini (Hemiptera, Heteroptera, Miridae, Isometopinae) from Brunei - Taszakowski, Artur; Kim, Junggon; Damken, Claas; Wahab, Rodzay A.; Herczek, Aleksander; Jung, Sunghoon (Zootaxa, 2021)
The new genus Megalofaciatus gen. nov. represented by two new species M. foliotibialis Taszakowski, Kim & Herczek sp. nov. (the type species) and M. gibbosus sp. nov. Taszakowski, Kim & Herczek (Hemiptera, Heteroptera, Miridae, Isometopinae, Gigantometopini), is described from Brunei. Photographs of the adult males and genital structures, as well as detailed SEM micrographs, are presented. The first finding of the largely modified leg in Gigantometopini is also reported.